Studi Kawasan Kerentanan Tanah Longsor Pada Ruas Jalan Poros di Kecamatan Enrekang Menggunakan Aplikasi ArcGis - Satrama; Sulfanita, Andi; Hamka (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
The prevalence of landslides has resulted in great losses, including the loss of human lives, the loss of property, and the disruption of natural ecosystems, especially in Enrekang District, Enrekang Regency. This study aims to identify landslide-prone areas and the level of landslide risk by using a landslide-prone map in Enrekang District. This study uses quantitative descriptive method techniques, spatial analysis with GIS analysis tools, and assessment analysis is carried out by multiplying the weight values and scores for variables such as slope, rainfall, soil rock type, and land use. The results of the study showed that three classes of vulnerability were obtained in Enrekang District, namely, high vulnerability with an area of 128.80 Ha, medium vulnerability with an area of 24033.26 Ha, and low vulnerability with an area of 3817.16 Ha.